Development and evaluation of an educational video for families on the relief of acute pain in babies - Ariadne Pinheiro Nazario; Vanessa Ferreira de Lima; Luciana Mara Monti Fonseca; Adriana Moraes Leite; Carmen Gracinda Silvan Scochi (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To develop and evaluate an educational video for active family participation in the relief of acute pain in babies. Methods A methodological and experimental study produced at the University of São Paulo at Ribeirão Preto School of Nursing and at a university hospital in southeastern Brazil, conducted in three operational stages, from January to July 2017. Results The video lasts nine minutes and 31 seconds, and it was validated by 19 expert judges with a 90% agreement among them for content and appearance items. Regarding the evaluation, 16 family members and pregnant women did it and were favorable to its use as an educational technology for learning. Conclusions Both the experts and the target population positively evaluated the video, which can be used as a health education strategy to empower families to engage in the baby pain relief with more autonomy and proactivity.